Benefits of an intervention programme with racket sports in primary school students - Emilio J Ruiz-Malagón; Gabriel Delgado-García; Elena López-Gutiérrez; Felix Zurita-Ortega; Víctor M. Soto-Hermoso (Universidad de Granada, 2020)
This experimental study is aimed at implementing a one-month racket sports programme within a sample of students aged 9 to 13 years in order to analyze its motivational climate effects during physical education lessons in a primary school context. The intervention programme was carried out on 40 of the 285 participants, the rest of the sample were used for descriptive purposes. The subjects participated voluntarily and were randomly assigned to one of two groups: control (n = 20) and experimental (n = 20). The programme consisted of eight sessions of different racket sports (tennis, paddle, badminton and table tennis). Motivational climate was extracted from the "Questionnaire of Motivational Climate Perceived in Sport" (PMCSQ-2). PMCSQ-2 reported two dimensions, task and ego. Regarding the results obtained, no changes were found in the control group. However, in the experimental group there was a significant increase (P < 0.05) in the orientation towards the task (3.22 vs 4.36), leading to the detriment of the ego orientation (3.4 vs 2.25). Thus, racket sports activity seem to be adequate to change motivational orientation towards the task, which has been reported to increase intrinsic motivation and to reduce stress and anxiety in physical education lessons.